Vpliv značilnosti slovenskega smrekovega konstrukcijskega žaganega lesa na njegove mehanske lastnosti in prevedba sortirnih razredov v trdnostne - Šega, Bogdan (Les (Ljubljana), 2010)
We present correlations between visually determined characteristics of structural sawn timber produced from Slovenian spruce (Picea abies (L.) Karst.) and its mechanical properties. Dried sawn timber was visually graded into sorting classes according to SIST DIN 4074-1. Results of visual grading were compared with grade determining properties (bending strength, modulus of elasticity and density). The main strength reducing charasteristics were the rate of growth (r =- 0.52), knot ratio (r =- 0.50), twist (r =- 0.23) and distance from the pith (r = 0.12). The most decisive factors to judge lower grade were however knots, followed by twist, the presence of pith and rate of growth. 10% of the specimens were graded to class S13, 58% to class S10, 15% to class S7, 17% of the specimens were rejected. The determined characteristicvalues of sorting classes S13, S10 and S7 were higher than the requirements of SIST EN 338 for the strength classes C30, C24 and C18 respectively. The results of this study represent a basis on which visual grades can be assigned to a strength classes.
Keywords: žagan les; smreka; razvrščanje; mehanske lastnosti; trdnost